The Impact of Artisanal Refinery on Bacterial Community in the Soil from Selected Areas in Rivers and Bayelsa States, Nigeria - Iworiso, D. P.; Daokoru-Olukole, C. G. (European Journal of Applied Sciences, 2025)
The soil, which is an intricate and dynamic biological system harboring a vast array of organisms, is directly affected by human activities as well as activities of illegal crude oil artisanal refineries. These activities have led to the introduction of hydrocarbons that range in high level toxicity and danger to human health. Hence creating problems for the ecological system. This study investigates the impact of artisanal crude oil refinery activities on soil bacterial communities in the Niger Delta regions, Okarki, Ododa (Rivers State), and Agba (Bayelsa State). Soil samples were collected and analysed following standard microbiological procedures, while the molecular method was used to characterize the bacterial isolates. Total petroleum hydrocarbon (TPH) concentration of soil samples was also analysed. The results of the bacteria count obtained from the soil samples for Total Heterotrophic Bacteria Count (THBC) ranged from 3.53 x 103 to 5.01 x 103 CFU/g, while Hydrocarbon Utilizing Bacteria Count (HUBC) ranged from 2.46 x 103 to 3.20 x 103 CFU/g. Total petroleum hydrocarbon (TPH) concentrations ranged from 107 to 7489 mg/kg around the refinery sites, which indicates soil contamination potential. The bacteria species identified were Bacillus, Staphylococcus, Pseudomonans, Brucella, Acinetobacter, Enterobacter, and Enterococcus. The molecular identification method reveals the following bacteria strains as Bacillus cereus, Brucella anthropi, and Stenotrophomonas maltophilia. The study emphasizes the intricate nature of soil microbial communities in artisanal refinery-affected regions and the need for long-term research to understand ecological impacts. It calls for effective mitigation strategies and stresses the importance of sustainable environmental management to address challenges posed by illegal artisanal crude oil refineries, advocating for a comprehensive approach.